2016
DOI: 10.1089/scd.2016.0158
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Tungstate for Promoting Mesenchymal Stem Cell Chondrogenesis

Abstract: Articular cartilage has a limited ability to heal. Mesenchymal stem cells (MSCs) derived from the bone marrow have shown promise as a cell type for cartilage regeneration strategies. In this study, sodium tungstate (Na 2 WO 4 ), which is an insulin mimetic, was evaluated for the first time as an inductive factor to enhance human MSC chondrogenesis. MSCs were seeded onto three-dimensional electrospun scaffolds in growth medium (GM), complete chondrogenic induction medium (CCM) containing insulin, and CCM withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…IGF-1 has been shown to enhance MSC chondrogenesis by promoting proliferation and expression of chondrocyte markers independently from TGF-β signaling (Longobardi et al, 2006). Although the chondrogenic medium has insulin, sodium tungstate and vanadium, which are also insulin mimetics, were found to enhance chondrogenesis and osteogenesis, respectively, synergistically with insulin (Khader et al, 2016;Schussler et al, 2017). transition between G1 to S and G2 to M phases (Santala et al, 2014), was high for cells on 2.5%, 5%, and 10% ZnO composite scaffolds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IGF-1 has been shown to enhance MSC chondrogenesis by promoting proliferation and expression of chondrocyte markers independently from TGF-β signaling (Longobardi et al, 2006). Although the chondrogenic medium has insulin, sodium tungstate and vanadium, which are also insulin mimetics, were found to enhance chondrogenesis and osteogenesis, respectively, synergistically with insulin (Khader et al, 2016;Schussler et al, 2017). transition between G1 to S and G2 to M phases (Santala et al, 2014), was high for cells on 2.5%, 5%, and 10% ZnO composite scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Relative gene expression of Runx2, SP7 (osterix), BGLAP (osteocalcin), and vascular endothelial growth factor (VEGF) were determined for osteogenesis. Samples ( n = 5 per group) were harvested and digested using TRIzol™ reagent (Fisher Scientific) according to manufacturer's protocol followed by isolating the RNA using RNeasy Micro Kit (Qiagen) that includes DNA digestion step (RNase Free DNase Set; Qiagen).Quantitative RT‐PCR analysis was evaluated according to previously published protocol (Khader et al, ). The value of each gene was normalized to the reference gene ribosomal protein, large, P0 (RPLP0) for the same sample (Δ C T ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Recent studies have shown that adipose-derived stem cells (ADSCs) and mesenchymal stem cells (MSCs) have promise for use in tissue repair due to their multi-directional differentiation abilities. 2830 MSCs are derived from the mesoderm during early embryonic development and are pluripotent stem cells that can differentiate into bone, cartilage, fat, and other cell types under specific induction conditions. 3136 As a subtype of MSCs, ADSCs are ideal stem cells for the regeneration of bone tissue.…”
Section: Gene Therapy Strategy For Bone Tissue Engineeringmentioning
confidence: 99%
“…Some of the many beneficial antidiabetic and antiobesity effects of Na 2 WO 4 (Table 1) have been recently and extensively reviewed (Bertinat, Nualart, Li, Yanez, & Gomis, 2015): Normalization of blood glucose and triglyceride levels (Munoz et al, 2001;Nocito et al, 2012); restoration of hepatic glucose metabolism through inhibition of gluconeogenesis and stimulation of glycogen synthesis (Barberà et al, 2001(Barberà et al, , 1994Munoz et al, 2001;Nocito et al, 2012); and induction of weight loss through complex antiobesity mechanisms (Amigo-Correig et al, 2011), among others, with the very unique characteristic that it does not produce hypoglycemic episodes. Other positive effects of Na 2 WO 4 have been reported in the last few years, such as protection of epithelial integrity in renal cells (Bertinat, Silva, et al, 2015), induction of chondrogenic differentiation of bone marrow-derived mesenchymal stem cells for cartilage regeneration strategies (Khader, Sherman, Rameshwar, & Arinzeh, 2016), protection of visual pathways (Bulut et al, 2016), improvement of reduced bone mechanical quality (Donmez et al, 2014), and antiplatelet activity (Fernandez-Ruiz et al, 2015). Given the entire spectrum of positive effects, Na 2 WO 4 has received considerable attention in the search for new antidiabetic drugs during the last two decades, having yielded very promising results.…”
mentioning
confidence: 99%